Systematic Literature Review of Contextual Interactive E-Modules Enhancing Students’ Creativity and Engagement in Mathematics - Hilda Widia Rita Hamid; Margaret vinsensia chelly Weroh (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The use of technology in education was an important innovation to support the learning process, especially mathematics, which was often considered difficult and uninteresting by students. The low creativity and activeness of students in learning mathematics indicated the need for the development of more interactive and contextual learning media. The writing of this article aimed to contribute to the literature on the development of the interavtive learning media based on a contextual approach through the development of interactive e-modules to enhance students’ creativity and activeness. This approach was chosen to help students connect mathematical concepts with real life, thereby improving their understanding, creativity, and activeness in learning. The method used in this study was the SLR (Systematic Literature Review) method by analyzing 18 source articles using relevant databases such as Google Scholar, Open Knowledge, Research Rabbit, and Semantics. The literature review results showed that the development of contextual-based interactive e-modules had the potential to encourage students’ creativity and activeness in learning mathematics more effectively and practically in real-life applications. Moreover, the development of contextual-based interactive e-modules also aligned with the demands of 21st-century learning, which emphasized critical thinking, creative thinking, communication, and collaboration skills. Therefore, this innovation in learing media also prepared students to face challenges in the digitalization era